2009
DOI: 10.1016/j.heares.2008.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hair cell regeneration in the mouse utricle following gentamicin ototoxicity

Abstract: Whereas most epithelial tissues turn-over and regenerate after a traumatic lesion, this restorative ability is diminished in the sensory epithelia of the inner ear; it is absent in the cochlea and exists only in a limited capacity in the vestibular epithelium. The extent of regeneration in vestibular hair cells has been characterized for several mammalian species including guinea pig, rat, and chinchilla, but not yet in mouse. As the fundamental model species for investigating hereditary disease, the mouse can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
162
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 33 publications
7
162
1
2
Order By: Relevance
“…Since it is currently unknown how many new hair cells would be required to noticeably restore function in a damaged crista, the stimulation of hair cell regeneration by DAPT treatment that we have demonstrated may have some therapeutic relevance (Kopke et al 2001). Though very promising, the number of hair cells generated here is likely insufficient to fully repair a damaged organ, which is also true of all other mammalian vestibular regeneration to date Warchol et al 1993;Rubel et al 1995;Tanyeri et al 1995;Li and Forge 1997;Lopez et al 2003;Kawamoto et al 2009;Lin et al 2011;Golub et al 2012;Jung et al 2013). In order to overcome these limitations on mammalian regeneration, we ultimately need a better understanding of the factors and pathways that mediate hair cell regeneration.…”
Section: Fig 8 Examples Of Lineage Traced Transitional Cells (Tc)mentioning
confidence: 84%
“…Since it is currently unknown how many new hair cells would be required to noticeably restore function in a damaged crista, the stimulation of hair cell regeneration by DAPT treatment that we have demonstrated may have some therapeutic relevance (Kopke et al 2001). Though very promising, the number of hair cells generated here is likely insufficient to fully repair a damaged organ, which is also true of all other mammalian vestibular regeneration to date Warchol et al 1993;Rubel et al 1995;Tanyeri et al 1995;Li and Forge 1997;Lopez et al 2003;Kawamoto et al 2009;Lin et al 2011;Golub et al 2012;Jung et al 2013). In order to overcome these limitations on mammalian regeneration, we ultimately need a better understanding of the factors and pathways that mediate hair cell regeneration.…”
Section: Fig 8 Examples Of Lineage Traced Transitional Cells (Tc)mentioning
confidence: 84%
“…In contrast, regenerative responses in mammalian ears are limited and appear largely ineffective Warchol et al 1993;Brigande and Heller 2009;Kawamoto et al 2009). Consistent with this, early investigations in rodents reported that the production of hair cells and supporting cells peaks during the second half of embryogenesis and declines precipitously before birth (Ruben 1967; Sans and Chat 1982; Lee et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In nonmammalian vertebrates, HCs are regenerated in both auditory and vestibular systems after HC loss, leading to functional recovery of hearing and balance function (1)(2)(3). In mammals, limited spontaneous HC regeneration occurs in the vestibular system (4)(5)(6)(7)(8). In the adult mammalian vestibular sensory epithelium, inner ear stem cells were isolated with the capacity to differentiate into HCs and other inner ear cell types (9).…”
mentioning
confidence: 99%